I want to proof

$\displaystyle s(n,k) = \sum_{m=k}^n{n^{m-k}s(n+1,m+1)}$

These are Stirling numbers of the first kind.

Any hints?

Printable View

- Feb 22nd 2010, 05:09 AMbram kierkelsStirling numbers
I want to proof

$\displaystyle s(n,k) = \sum_{m=k}^n{n^{m-k}s(n+1,m+1)}$

These are Stirling numbers of the first kind.

Any hints? - Feb 22nd 2010, 06:15 AMNonCommAlg
- Feb 22nd 2010, 07:52 AMbram kierkels
Yes, i know this relation. But in a slightly different version, now i see the solution. Thanks